Students with Autism Spectrum Disorders and Their First-Year College Experiences - Stefania D. Petcu (MDPI AG, 2021)
Using data from the 2019 CIRP Freshman Survey and the Your First College Year (YFCY) from the Higher Education Research Institute at UCLA, this study explores the differences between the characteristics and behaviors of the first-year students with autism spectrum disorders (17) and those of students with learning disabilities (102). The findings indicate that the characteristics of these two groups of first-year college students were similar except for gender, ethnicity, first college generation, and parents’ income. Compared with first-year college students with LD, students with ASD were less likely to engage in risk-taking behaviors, use health services and the writing center.